2018
DOI: 10.1038/s41467-017-02430-2
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative interactions between seed-borne bacterial and air-borne fungal pathogens on rice

Abstract: Bacterial-fungal interactions are widely found in distinct environments and contribute to ecosystem processes. Previous studies of these interactions have mostly been performed in soil, and only limited studies of aerial plant tissues have been conducted. Here we show that a seed-borne plant pathogenic bacterium, Burkholderia glumae (Bg), and an air-borne plant pathogenic fungus, Fusarium graminearum (Fg), interact to promote bacterial survival, bacterial and fungal dispersal, and disease progression on rice p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 64 publications
0
43
0
Order By: Relevance
“…In contrast, the overexpression mutant was more sensitive to oxidative stress. Further, the accumulation of intracellular ROS may have negatively influenced vegetative growth, and this negative effect may have been reversed by the addition of olive oil (Jung et al, 2018). …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the overexpression mutant was more sensitive to oxidative stress. Further, the accumulation of intracellular ROS may have negatively influenced vegetative growth, and this negative effect may have been reversed by the addition of olive oil (Jung et al, 2018). …”
Section: Discussionmentioning
confidence: 99%
“…We focused on F. graminearum and B. glumae in this study because there has been an increase in FHB and BPB in rice fields in Korea due to climate change [33,34]. In addition, we showed previously that F. graminearum plays an important role in the disease dispersal and survival of B. glumae [9]. Therefore, alternative compounds that have broad-spectrum activity against both fungi and bacteria, such as DPIC, are needed to control plant diseases, such as F. graminearum and B. glumae .…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria in the genera Burkholderia , Pseudomonas , and Ralstonia are major plant pathogens that exist widely in the environment [6–8]. Recently, it has been shown that Fusarium graminearum , which causes Fusarium head blight (FHB) and Burkholderia glumae , which causes bacterial panicle blight (BPB), interact cooperatively in their development and dispersal on rice [9]. This finding suggests that comprehensive studies are required to control plant diseases in fields.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, B. glumae can use additional strategies to efficiently induce severe disease. For example, B. glumae cooperatively interacts with the pathogenic fungus, Fusarium graminearum , promoting disease progression in rice ( Jung et al, 2018 ).…”
mentioning
confidence: 99%